Context shapes (proto)conversations in the first year of life - Laudańska, Zuzanna; Babis, Karolina; Kozioł, Agata; Szmytke, Magdalena; Marschik, Peter B.; Marschik, Dajie; Malinowska-Korczak, Anna; López Pérez, David; Tomalski, Przemysław (Developmental science, 2025)
Speech development occurs in highly variable environments; however, little is known about the effect of situational context on emerging infant vocalizations. At 4 time points (4, 6, 9, and 12 months), we longitudinally measured vocalizations of 104 White infant-caregiver dyads (41 girls) during three play contexts: book-sharing, toy play, and rattle-shaking. The frequency of infant vocalizations differed between contexts only at 12 months of age. Meanwhile, caregivers systematically spoke more frequently during book-sharing than in other contexts from 4 months of age onwards. Book-sharing elicited more conversational turns at the dyadic level than in other contexts from 9 months of age. Our results show emergence of vocal differentiation of play context by infants and the role of book-sharing in facilitating early vocal turn-taking.
Online veröffentlicht: 10. April 2025
Gesehen am 24.09.2025